Influência de agentes clareadores de uso caseiro e em consultório na resistência de união braquetes ao esmalte em diferentes tempos após clareamento - NUNES, Mauro de Amorim Acatauassú (São Leopoldo Mandic, 2017)
The aim of this study was to evaluate the influence of bleaching agents on the shear bond strength of metal orthodontic brackets to enamel using a resin cementing agent; and fracture mode, at different time intervals after bleaching treatment. One-hundred-and-eighty bovine permanent incisors were sectioned and randomly divided into three groups: Group I - (control): without bleaching. Group 2: bleached with 20% Carbamide Peroxide, (Opalescence® PF) for 21 days, 10 hours/day. Group 3: bleached with 38% Hydrogen Peroxide, (Opalescence® Boost™) in two 15-minute applications every 7 days (for 21 days). After this, the groups bleached were again divided into sub-groups (n=15) according to the time interval after bleaching to perform procedures for bracket bonding to enamel: immediate, 24 hours, 7, 14, 21 and 28 days. The shear bond strength tests were performed in a universal test machine (EMIC) at a speed of 0.5mm/min and the values were recorded in MPa. After, the teeth were examined under a stereoscopic loupe at 40X magnification, to record the Adhesive Remnant Index (ARI). ANOVA showed the technique x time interaction was significant (p=0.0310). Scores were analyzed by Kruskal Wallis and Dunn tests for comparisons between times and Mann Whitney; between techniques, and comparisons with control group. The level of significance considered was 5%. As regards the Group 2, there was no statistically significant difference among time intervals. For the Group 3, there was lower bond strength of brackets to enamel in the immediate time, and this time also differed statistically from that of the Control group. Immediate time did not differ statistically from the times at 14 and 21 days. Times between 1 and 28 days also did not differ statistically among them. The fractures, were a larger number of the cohesive type at the bracket/ orthodontic resin interface. For the group in which 38% Hydrogen Peroxide was used, adhesive fractures in the enamel/ orthodontic resin region were predominant in the immediate time. Use of 20% Carbamide Peroxide, had no influence on the bond strength of orthodontic brackets; whereas the use of 38% Hydrogen Peroxide immediately before bracket bonding reduced the shear bond strength. Performing bracket bonding immediately after conclusion of bleaching treatment must be contra-indicated.